Coincidence and common fixed points of weakly reciprocally continuous and compatible hybrid mappings via an implicit relation and an application - Chauhan, Sunny; Imdad, Mohammad; Kadelburg, Zoran; Vetro, Calogero (Sarajevo journal of mathematics, 2025)
Using the hybrid version of the notion of weakly reciprocally continuous pairs of mappings due to Gairola et al. [Coincidence and fixed point for weakly reciprocally continuous single-valued and multi-valued maps, Demonstratio Math. (2013/2014), accepted], we prove a coincidence and common fixed point theorem for a hybrid pair of compatible mappings via an implicit relation. Our main result improves and generalizes a host of previously known theorems. As an application, we give a homotopy theorem which supports our main result.